2013
DOI: 10.1016/j.jpsychires.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of odor valence on olfactory performance in schizophrenia patients, unaffected relatives and at-risk youth

Abstract: Given the presence of odor identification impairment in individuals with schizophrenia and recent evidence of aberrant odor hedonic processing, the aim of this investigation was to examine the influence of valence and intensity on odor identification in schizophrenia patients, their first-degree family members, and young persons at clinical risk for psychosis. Participants completed the 16-item Sniffin’ Stick Odor Identification Test. A logistic regression was conducted to assess the influence of valence and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
(49 reference statements)
1
11
0
5
Order By: Relevance
“…Our findings of more severe impairment in odor identification in bipolar patients with psychosis vs those without, coupled with greater impairment for hedonically pleasant versus unpleasant/neutral odors, directly mirror what has previously been reported both for schizophrenia patients and clinical high‐risk youth . While initial high‐risk studies suggested that olfactory impairments might be specific predictors of actual conversion to schizophrenia, more recent data suggest that this is an index of poor functional outcome which may include overt psychosis, but which is an ominous marker of neurodevelopmental aberration independent of future diagnosis.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our findings of more severe impairment in odor identification in bipolar patients with psychosis vs those without, coupled with greater impairment for hedonically pleasant versus unpleasant/neutral odors, directly mirror what has previously been reported both for schizophrenia patients and clinical high‐risk youth . While initial high‐risk studies suggested that olfactory impairments might be specific predictors of actual conversion to schizophrenia, more recent data suggest that this is an index of poor functional outcome which may include overt psychosis, but which is an ominous marker of neurodevelopmental aberration independent of future diagnosis.…”
Section: Discussionsupporting
confidence: 85%
“…In this latter study, patients with bipolar and unipolar depression were found to rate tastants and odorants similarly to each other and a control group. Conversely, schizophrenia patients underrate the pleasantness of pleasant stimuli and show poorer identification accuracy for pleasant odors . Notably, Kotlicka‐Antczak et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue is discussed in [18•]. Several original articles on the topic have been published in the past years, e.g., [19][20][21][22]. By examining patients with schizophrenia (n=65), first-degree relatives (n=24) as well as youths at clinical (n=10) or genetic risk (n=14) for schizophrenia, isolated deficits in odor identification were identified as genetic markers of vulnerability for schizophrenia, while odor discrimination deficits were proposed as possible biomarkers associated with the development of overt schizophrenia [23].…”
Section: Olfactory Function and Schizophreniamentioning
confidence: 99%
“…our use of Craigslist) and characteristics associated with participation in a time-intensive research study, which may obscure a potential deficit in the CHR subjects with whom they are compared. This may also explain our prior finding of equivalent smell identification between CHR patients and controls in a subgroup of our current cohort (Kayser et al, 2013), who were assessed with Sniffin’ Sticks (Hummel et al, 1997), which is in contrast to a cross-sectional study of CHR subjects using this same method (Kamath et al, 2013). …”
Section: Discussionmentioning
confidence: 77%